Riffaterre’s semiotic reading of yā nahḍat al-’ulamā’: Ideological reverence and spiritual loyalty in pesantren poetry - Imam Bonjol Juhari; Sri Wahyuni; Fadiah Alfi Laila; Delfarianto (Diwan: Jurnal Bahasa dan Sastra Arab, 2026)
Although pesantren poetry occupies a distinctive place within Indonesian Islamic literary tradition, it remains largely overlooked in semiotic scholarship. The poem Yā Nahḍat al-ʿUlamāʾ, composed by KH. Fuad Hasyim, as a devotional expression of Nahdlatul Ulama's religious identity, has received no sustained academic attention whatsoever in this context. This study fills that gap by examining how the poem constructs ideological meaning through Riffaterre's semiotic framework. Using a descriptive-qualitative approach, the analysis proceeds through heuristic and hermeneutic readings, identifies mechanisms of indirect expression, and reconstructs the poem's semiotic structures across its fifteen stanzas. The poem derives from a single matrix, Nahdlatul Ulama, as a source of light, protection, and supplication. This proposition is never stated outright but realized through imagery that moves steadily from the personal toward the cosmic and collective. Displacement and distortion draw on the conventions of the ghazal and the madāḥ qaṣīdah to legitimize institutional devotion, while recurring vocative formulas accumulate a performative weight comparable to dhikr. These findings demonstrate that ideological meaning in religious poetry operates through linguistic architecture rather than through explicit doctrinal statement. The study offers a replicable semiotic methodology for analyzing pesantren literature, and it illuminates how contemporary Indonesian Islamic organizations draw on poetic tradition to construct, reinforce, and sustain collective ideological identity. These findings also open productive directions for future research into the intersection of literary form, religious practice, and ideological production in Muslim societies more broadly.